Structural and dynamical properties of dilute gel networks in colloid–polymer mixtures - Gimperlein, Matthias; Schmiedeberg, Michael (Journal of Chemical Physics, 2021)
The competition of short-ranged depletion attraction and long-ranged repulsion between colloidal particles in colloid–polymer mixtures leads to the formation of heterogeneous gel-like structures. Our special focus will be on the states where the colloids arrange in thin strands that span the whole system and that we will refer to as dilute gel networks. These states occur at low packing fractions for attractions that are stronger than those at both the binodal line of the equilibrium gas–liquid phase separation and the directed percolation transition line. By using Brownian dynamics simulations, we explore the formation, structure, and aging dynamics of dilute gel networks. The essential connections in a dilute gel network are determined by constructing reduced networks. We compare the observed properties to those of clumpy gels or cluster fluids. Our results demonstrate that both the structure and the (often slow) dynamics of the stable or meta-stable heterogeneous states in colloid–polymer mixtures possess distinct features on various length and time scales and thus are richly divers
Keywords: colloidal gel; colloid-polymer mixture; gel network